IMPLEMENTASI TATA TERTIB SEKOLAH PADA SISWA KELAS VIII I DI MTs NEGERI 2 PONTIANAK - Oliviani, Melisa; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTitle of this research is "Implementation of school rules for students of class VIII I in Pontianak State 2 MTs." This study aimed to determine the general problems in this study, namely "How is the implementation of school rules for class VIII I students in Pontianak 2 MTs.".With sub-problems: (1) How is the implementation of school rules for students of class VIII I in MTs Negeri 2 Pontianak in preventive aspects, (2) How is the implementation of school rules for class VIII I students in MTs Negeri 2 Pontianak in repressive aspects. The form of research used in this study is qualitative research with descriptive research methods. Data collection techniques used were observation, interviews, and documentation. The results of this study are that the implementation of school discipline in preventive aspects and repressive aspects can be concluded and has been implemented well, although there are some students who are found to still violate the rules that apply in the school. Keywords:  Implementation, School Rules